유동층보일러 연소로 마모방지장치 개발을 위한 유동해석 분석 - 이웅근; 김동욱; 박상철 (한국설비안전학회지, 2020)
In power plant industry, the pulverized coal boiler has been the main type for many decades because of low fuel cost, large capacity, and high efficiency. Circulating fluidized bed combustion boiler(CFBC), however, is being a growing interest worldwide because of the reduction of pollutant gas emission compared to the pulverized coal boiler. The CFBC boiler is an eco-friendly facility that makes complete combustion via the ‘circulation’ of bed material and unburned coal. The circulation, however, may cause serious erosion problems of the boiler wall and heat tube. Because of the erosion problems, the risk of emergency shut down of CFBC boiler gets high. To cope with the problem, we propose optimized erosion protection plates by using ANSYS CFX in this paper. The variables of the plates include the size of plate and location, the proposed erosion protection plates are verified through the real installation in a CFBC boiler.
Keywords: Ash Erosion; Erosion Reduction Device; CFC(Computational Fluid Dynamics); ANSYS CFX; Circulation